Epigenetic study of the long-term effects of gulf War illness - Jones, B. C.; O’Callaghan, J. P.; Ashbrook, D. G.; Lu, L.; Prins, P.; Zhao, W.; Mozhui, K. (Frontiers in Genetics, 2025)
IntroductionGulf War Illness is a chronic multisymptomatic disorder that affects as many as 25-35% of the military personnel who were sent to the Persian Gulf war in 1991. The illness has many debilitating symptoms, including cognitive problems, gastrointestinal symptoms, and musculoskeletal pain. Those so afflicted have been sick for more than 30 years and, therefore, it has become imperative to understand the etiology of Gulf War Illness and then produce treatments to ease the symptoms. We hypothesized that the length of the disease was reflected in epigenetic modification of possibly several genes related to the symptoms.MethodsWe subjected male and female mice from 11 BXD strains to combined corticosterone and the sarin surrogate, diisopropylfluorophosphate, to emulate the physiological stress of war and the potential exposures to organophosphate pesticides and nerve agent in theater. Three hundred days after treatment, we used Methyl-CpG-binding domain sequencing (MBD-seq) to assay genome-wide methylation.ResultsThe analysis revealed 20 methylated genes, notably Eif2b5, that regulates myelin production.DiscussionLoss of myelin with accompanying musculoskeletal pain is a major symptom of Gulf War Illness. Our work demonstrates multiple genes were methylated by exposure to organophosphates and glucocorticoids. These genes point to biochemical mechanisms that may be targets for therapeutic intervention.